Fundamentals Of Theory and Methodology Of Physical Education and Sports - Abbasov Bakhadir Asatillaevich (Indonesian Journal Publisher, 2025)
This study examines the theoretical and methodological foundations of physical education and sports, focusing on the relationship between physical culture, education, and sports science. The research aims to analyze trends in sports development, training methodologies, and their integration with other scientific disciplines. A mixed-methods approach, including literature review and practical case studies, is used to explore the effectiveness of modern training strategies. The findings emphasize the importance of a scientific approach in improving athletic performance and sports education.